Tough Decision Making in Pembrolizumab-Associated Acute Interstitial Nephritis: A Case Report - João Grilo; Joana Coutinho; Mário Góis; Catarina Reis Santos; Rui Alves Filipe; Ernesto Rocha (Publicações Ciência e Vida, 2023)
Pembrolizumab is an immune checkpoint inhibitor used as a cancer therapy. The incidence of immune related adverse events in patients receiving immune checkpoint inhibitors can be as high as 59%-85%. Renal adverse effects are uncommon, but the incidence of kidney toxicity related to pembrolizumab is rising as the use of this agent becomes more frequent. We present an uncommon case of biopsy-proven acute interstitial nephritis secondary to pembrolizumab in a patient with metastatic squamous cell carcinoma at the time of his fourth scheduled cycle. Despite the good initial tumor response, pembrolizumab had to be suspended and the patient started on corticosteroids with an initial good response. On his own initiative, the patient stopped prednisolone early, leading to a rebound acute kidney injury. Pembrolizumab was not reintroduced for the risk of further renal function worsening. His clinical status declined due to the progression of the neoplastic disease, and he was referred for palliative care. This case illustrates the importance of systematizing some key points in the approach to acute interstitial nephritis secondary to pembrolizumab: the role of the differential diagnosis of acute kidney injury in a patient under an immune checkpoint inhibitor, the role of glucocorticoids and the controversy about rechallenging this drug after a related acute interstitial nephritis.